2015
DOI: 10.1088/0029-5515/55/8/083002
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous oscillation prior to disruption caused by kink modes in HL-2A tokamak plasmas

Abstract: A class of evident MHD activities prior to major disruption has been observed during recent radiation induced disruptions of the HL-2A tokamak discharges. It can be named SOD, synchronous oscillations prior to disruption, characterized by synchronous oscillation of electron cyclotron emission (ECE), core soft x-ray, Mirnov coil, and a D radiation signals at the divertor plate. The SOD activity is mostly observed in a parametric regime where the poloidal beta is low enough before disruption, typically correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Actually, the preflare-VLP is much alike the quasi-periodic oscillations in precursor phase of a Tokamaks major disruption (Wesson 1997, Jiang et al 2015. The precursor phase (similar to the preflare phase) lasts for typically 10 ms and the fast phase (similar to the flare rising phase) for about 1 ms at medium-sized Tokamaks.…”
Section: Generation Mechanism Of Preflare-vlpmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, the preflare-VLP is much alike the quasi-periodic oscillations in precursor phase of a Tokamaks major disruption (Wesson 1997, Jiang et al 2015. The precursor phase (similar to the preflare phase) lasts for typically 10 ms and the fast phase (similar to the flare rising phase) for about 1 ms at medium-sized Tokamaks.…”
Section: Generation Mechanism Of Preflare-vlpmentioning
confidence: 97%
“…The precursor phase (similar to the preflare phase) lasts for typically 10 ms and the fast phase (similar to the flare rising phase) for about 1 ms at medium-sized Tokamaks. Because of electric currents and limited resistivity, the tearing-mode instability can produce the growth of magnetic oscillations of an m=2 mode in the precursor phase of Tokamak major disruptions (Jiang et al 2015).…”
Section: Generation Mechanism Of Preflare-vlpmentioning
confidence: 99%
“…Furthermore, on the basis of a systematic and detailed statistical analysis of a large database, it was also shown that the JET and COMPASS data were consistent with each other in terms of amplitude of asymmetries and their rotation behaviour-an important result that can prove useful for model development and making load predictions for ITER. Characterization studies of the HL-2A tokamak discharges have identified a precursor mode that always appears to precede the onset of disruptions at the density limit or radiation induced disruptions [4]. It is observed as a synchronous oscillation superposed on the soft x-ray (SXR), electron cyclotron emission (ECE), Mirnov and H α radiation line signals.…”
Section: Disruptions and Runaway Electronsmentioning
confidence: 99%
“…Moreover, if left uncontrolled, nonlinearly unstable resistive kinks (Jiang et al. 2015) or thermally unstable tearing modes (Gates & Delgato-Aparicio 2012; White, Gates & Brennan 2015) may grow to a large amplitude and trigger disruption. Thus it is of utmost importance to have a thorough understanding of the stability of resistive modes in both the linear and nonlinear phases.…”
Section: Introductionmentioning
confidence: 99%
“…In tokamaks, tearing modes and resistive kink modes may arise from unfavourable current density profiles which drive reconnection at corresponding resonant surfaces, resulting in the formation of magnetic islands which tend to cause confinement degradation (Chang & Callen 1990). Moreover, if left uncontrolled, nonlinearly unstable resistive kinks (Jiang et al 2015) or thermally unstable tearing modes (Gates & Delgato-Aparicio 2012;White, Gates & Brennan 2015) may grow to a large amplitude and trigger disruption. Thus it is of utmost importance to have a thorough understanding of the stability of resistive modes in both the linear and nonlinear phases.…”
Section: Introductionmentioning
confidence: 99%